The Rise of Deepfake Technology: Implications for Truth, Trust and Media Manipulation - Pandey, Abhishek Anil; Doshi, Kinjal (Journal of Advanced Research in Applied Artificial Intelligence and Neural Network, 2024)
This article explores the rise of deepfake technology in all aspects and how it is dangerous for any person. Deepfake technology is one of the most hazardous tools to damage a person’s integrity. The advent of deepfake technology, powered by artificial intelligence, presents a formidable challenge to truth, trust, and media integrity. This article also explores the far-reaching implications of deepfakes on these fundamental aspects, highlighting the erosion of trust in information sources and the potential for widespread misinformation. The ability of deepfakes to convincingly manipulate audio-visual content intensifies the existing hurdles in media manipulation, threatening the credibility of individuals and institutions. To address this, the article advocates for innovative detection methods and countermeasures, emphasising the role of machine learning, collaborative efforts, and emerging technologies such as blockchain. The pursuit of these strategies is crucial to navigating the evolving landscape of deepfake threats and preserving the authenticity of information in the digital age.